Table olives from the Northeast of Portugal: basis for a new protected designation of origin azeitonas de mesa transmontanas - Pereira, Ermelinda (2014)
Table olives are one of the most popular agro-fermented food products in the Mediterranean basin. In Portugal, there is a great tradition of table olives production, being Trás-os-Montes one of the most important producing regions. Their tradition, sensorial and chemical characteristics justify the creation of a new Protected Designation of Origin “Azeitonas de mesa Transmontanas”. In this context, the objective of the present work was to contribute for the collection of supporting basis for the PDO creation and implementation. Table olives processed by natural fermentation were collected from different local producers. The morphological, chemical (moisture, crude protein, total fat, ash, carbohydrates, fatty acids, tocopherols and phenolic) and microbial (yeast population on the final stage of fermentation) attributes were characterized. All samples were also analyzed for their microbial safety (aerobic mesophilic, yeasts, coliforms, E. coli, sulfite-reducing clostridia, S. aureus and Salmonella spp). “Azeitonas de mesa Transmontanas” are produced mainly by Cvs Cobrançosa and Negrinha de Freixo; water is the major constituent (62.9% to 78.4%), followed by fat (10.2% and 26.6%), that is mainly monounsaturated, being oleic the major fatty acid (68.3% to 83.0%). Crude protein and ash content ranged between 2.9-4.6% and 3.3-7.1%, respectively. Ten phenolic compounds were identified and quantified and hydroxytyrosol was the major one. Yeasts populations were mainly Candida ishiwadae, C. boidinii, Pichia membranifaciens, P. manshurica, Sporobolomyces roseus and Wickerhamomyces anomalus, being all samples safe for consumption.